2009
DOI: 10.4076/1757-1626-2-8594
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure pulmonary edema in the prone position: a case report

Abstract: Acute airway obstruction can result in life - threatening pulmonary edema. It can develop rapidly, without warning, in otherwise healthy patients. Negative pressure pulmonary edema has been described after acute airway obstruction in situations when a patient is breathing against an obstructed airway such as croup, epiglottitis or laryngospasm. In the following case, we observed a rare occurrence of pulmonary edema in a female following sedation in the prone position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…3 Its true incidence is unknown; some authors indicate that it is produced in 11% of patients who require an active intervention of the airway for acute obstruction. 4,5 In our review, we found 34 cases reported, mostly male (26/34 or 76%). 7,8 Average age was 31 years (range: 14---67 years).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…3 Its true incidence is unknown; some authors indicate that it is produced in 11% of patients who require an active intervention of the airway for acute obstruction. 4,5 In our review, we found 34 cases reported, mostly male (26/34 or 76%). 7,8 Average age was 31 years (range: 14---67 years).…”
Section: Discussionmentioning
confidence: 87%
“…14 A respiratory clinical exam during the immediate postoperative period will identify the presence of signs of lung oedema, as long as the presence of stridor, pulmonary crackling and respiratory insufficiency, assessed using pulse oxygen analysis, are taken into account. 4,10,12 Spontaneous resolution of the entity in mild cases and resolution with few therapeutic measures contribute to the under diagnosis of the problem. It should be emphasised that it is important to keep this condition in mind following any type of surgical intervention in healthy, young patients who present hypoxaemia not explained by other causes and establish the therapeutic measures needed to avoid an unfavourable patient evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, the most frequently known cause of NPPE in adults is laryngospasm after extubation 8,9 . It has been reported that NPPE is more common in healthy young adults who have well-developed inspiratory muscles and can generate this pressure easily 10 .…”
Section: Discussionmentioning
confidence: 99%